2019
DOI: 10.1055/s-0038-1676781
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Comparison of Adjustment Protocols of Personal Sound Amplification Products

Abstract: The Over-the-Counter Hearing Aid Act of 2017 was signed into law in August 2017 and facilitates the introduction of direct-to-consumer sales of hearing aids for adults with mild-to-moderate hearing loss. Among many questions surrounding over-the-counter sales is the ability of users to self-fit amplification. Many studies have conducted self-fitting procedures using guidance materials provided by audiologists. In this pilot, we explore the ability of users to self-adjust personal sound amplification devices us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Likewise, Perry, et al [42] found that some different algorithms for self-fitting of the Ear Machine app may reduce speech intelligibility. Additionally, a study by Oliver, et al [8] showed that the audiologist protocol gave better fitting results, based on the NAL-NL2 prescription procedure [43], than the two user-driven protocols.…”
Section: Self-fitting Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Likewise, Perry, et al [42] found that some different algorithms for self-fitting of the Ear Machine app may reduce speech intelligibility. Additionally, a study by Oliver, et al [8] showed that the audiologist protocol gave better fitting results, based on the NAL-NL2 prescription procedure [43], than the two user-driven protocols.…”
Section: Self-fitting Systemsmentioning
confidence: 99%
“…According to the abovementioned studies [8,41,43], the use of smart devices for selftuning is highlighted, although cautiousness is needed for the elderly, who are less efficient in the use of technology and some do not even use smartphones. Moreover, these studies have highlighted the factor of confidence in one's ability to set the hearing aid to the optimal fitting value.…”
Section: Self-fitting Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior evidence has suggested that adults can significantly benefit from hearing aids provided through a consumer-driven model where they select and fit their own devices [ 17 , 18 , 19 ]. Specifically, word understanding, social interactions, and emotional well-being significantly increased after these consumer driven devices were provided.…”
Section: Introductionmentioning
confidence: 99%